Step-by-step explanation:
Let [tex]p1[/tex] be the point [tex](-1,4)[/tex]
Let [tex]p2[/tex] be the point [tex](3,-4)[/tex]
The equation of the line passing through two points [tex]p1=(x_{1},y_{1})[/tex]
and [tex]p2=(x_{2},y_{2})[/tex] is [tex]\frac{y-y_{1}}{x-x_{1}} =\frac{y_{2}-y_{1}}{x_{2}-x_{1}}[/tex]
substituting [tex]p1,p2[/tex] in the above equation yields
[tex]\frac{y-4}{x-(-1)}=\frac{-4-4}{3-(-1)}[/tex]
which when simplified gives [tex]\frac{y-4}{x+1}=\frac{-8}{4}[/tex]
which when further simplified gives [tex]2x+y=2[/tex]